Réponses

  • Utilisateur Brainly
2013-05-04T18:41:56+02:00

f(x)=(sin²(3x))/(cos(4x))

 

la dérivée de f est :

 

f'(x)=(3*2*sin(3x)*cos(3x)*cos(4x)-(-4)*sin(4x)*sin²(3x))/(cos²(4x))

      =(3*sin(6x)*cos(4x)+4*sin(4x)*sin²(3x))/(cos²(4x))

      =(sin(3x))((6*cos(3x)*cos(4x)+4*sin(4x)*sin(3x))/(cos²(4x)))

Meilleure réponse !
2013-05-04T18:50:17+02:00

je crois que prof07 n'a pas vu le V

y' = 2.3.sin3x.cos3x.Vcos4x -sin²3x.(4sin4x)/2.Vcos4x

   = 2sin3x( 3cos3x.Vcos4x - sin3x.sin4x/Vcos4x)

    = 2sin3x(3cos3x.cos4x - sin3x.sin4x)/Vcos4x